ERICA: prevalences of hypertension and obesity in Brazilian adolescents - Katia Vergetti Bloch; Carlos Henrique Klein; Moyses Szklo; Maria Cristina C Kuschnir; Gabriela de Azevedo Abreu; Laura Augusta Barufaldi; Gloria Valeria da Veiga; Beatriz Schaan; Thiago Luiz Nogueira da Silva; Maurício Teixeira Leite de Vasconcellos (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To estimate the prevalence of arterial hypertension and obesity and the population attributable fraction of hypertension that is due to obesity in Brazilian adolescents. METHODS Data from participants in the Brazilian Study of Cardiovascular Risks in Adolescents (ERICA), which was the first national school-based, cross-section study performed in Brazil were evaluated. The sample was divided into 32 geographical strata and clusters from 32 schools and classes, with regional and national representation. Obesity was classified using the body mass index according to age and sex. Arterial hypertension was defined when the average systolic or diastolic blood pressure was greater than or equal to the 95th percentile of the reference curve. Prevalences and 95% confidence intervals (95%CI) of arterial hypertension and obesity, both on a national basis and in the macro-regions of Brazil, were estimated by sex and age group, as were the fractions of hypertension attributable to obesity in the population. RESULTS We evaluated 73,399 students, 55.4% female, with an average age of 14.7 years (SD = 1.6). The prevalence of hypertension was 9.6% (95%CI 9.0-10.3); with the lowest being in the North, 8.4% (95%CI 7.7-9.2) and Northeast regions, 8.4% (95%CI 7.6-9.2), and the highest being in the South, 12.5% (95%CI 11.0-14.2). The prevalence of obesity was 8.4% (95%CI 7.9-8.9), which was lower in the North region and higher in the South region. The prevalences of arterial hypertension and obesity were higher in males. Obese adolescents presented a higher prevalence of hypertension, 28.4% (95%CI 25.5-31.2), than overweight adolescents, 15.4% (95%CI 17.0-13.8), or eutrophic adolescents, 6.3% (95%CI 5.6-7.0). The fraction of hypertension attributable to obesity was 17.8%. CONCLUSIONS ERICA was the first nationally representative Brazilian study providing prevalence estimates of hypertension in adolescents. Regional and sex differences were observed. The study indicates that the control of obesity would lower the prevalence of hypertension among Brazilian adolescents by 1/5.